2012
DOI: 10.1002/ajpa.22029
|View full text |Cite
|
Sign up to set email alerts
|

Incremental enamel development in modern human deciduous anterior teeth

Abstract: This study reconstructs incremental enamel development for a sample of modern human deciduous mandibular (n = 42) and maxillary (n = 42) anterior (incisors and canines) teeth. Results are compared between anterior teeth, and with previous research for deciduous molars (Mahoney: Am J Phys Anthropol 144 (2011) 204-214) to identify developmental differences along the tooth row. Two hypotheses are tested: Retzius line periodicity will remain constant in teeth from the same jaw and range from 6 to 12 days among ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
0
25

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 85 publications
8
78
0
25
Order By: Relevance
“…Determination of the position of NNL is the first step in all analyses regarding characteristics of the enamel formed in the prenatal and postnatal parts of ontogeny (Antoine et al, 2009;Beynon et al, 1998;Dean, 2009, 2014;Eli et al, 1989;Mahoney, 2011Mahoney, , 2012Sabel et al, 2008;Seow et al, 2005;Smith and Avishai, 2005;Żądzińska et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Determination of the position of NNL is the first step in all analyses regarding characteristics of the enamel formed in the prenatal and postnatal parts of ontogeny (Antoine et al, 2009;Beynon et al, 1998;Dean, 2009, 2014;Eli et al, 1989;Mahoney, 2011Mahoney, , 2012Sabel et al, 2008;Seow et al, 2005;Smith and Avishai, 2005;Żądzińska et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…FitzGerald et al 2006;Thomas 2003;Mahoney 2011Mahoney , 2012Birch -Dean 2014), které však vyžadují přípravu histologického prepará-tu a tudíž destrukci zubu. Díky rozvíjejícímu se oboru virtuální histologie je v poslední době možná i nedestruktivní analýza mikrostruktury zubů v 3D zobrazení pomocí rentgenové mikrotomografie (µCT) se synchrotronem jakožto zdrojem rentgenového záření a s využitím fázo-vého kontrastu (Smith -Tafforeau 2008).…”
Section: Studia Archaeologica Brunensia 21 / 2016 /unclassified
“…Within an individual, periodicity values are also consistent regardless of the tooth type, or the jaw arch from which the tooth is taken (FitzGerald, 1998; Reid et al, 1998; Mahoney, 2012). Nevertheless, inter-individual variations in striae periodicities have been noted.…”
Section: Introductionmentioning
confidence: 97%
“…Extensive studies have shown no difference between striae periodicities in different parts of a single tooth (Fukuhara, 1959; Beynon, 1992; FitzGerald, 1998; Mahoney, 2008, 2012). Within an individual, periodicity values are also consistent regardless of the tooth type, or the jaw arch from which the tooth is taken (FitzGerald, 1998; Reid et al, 1998; Mahoney, 2012).…”
Section: Introductionmentioning
confidence: 99%